2018
DOI: 10.3892/or.2018.6193
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan downregulates insulin-like growth factor-I receptor levels in HT-29 human colon cancer cells

Abstract: Fucoidan, a sulfated polysaccharide present in brown seaweed, has demonstrated anticancer activity in lung, breast, liver and colon cells. The insulin-like growth factor (IGF) signaling pathway regulates growth in HT-29 cells through the insulin receptor substrate-1 (IRS-1)/phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) and Ras/Raf/extracellular signal-regulated kinase (ERK) pathways. The aim of the present study was to investigate whether fucoidan downregulates the IGF-IR signaling pathway in HT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Thinh et al reported three fucoidan fractions (SmF1, SmF2, and SmF3) extracted from Sargassum mcclurei where all fractions were found to be less cytotoxic and exhibited inhibition of colony formation in colon cancer DLD-1 cells [ 92 ]. HT-29 cell death is induced by administration of fucoidan, the probable reason for which could be the downregulation of IGF-IR signaling via the IRS-1/PI3K/AKT pathway [ 93 ].…”
Section: Anticancer Potential Of Fucoidan: Insights From Recent Studiesmentioning
confidence: 99%
“…Thinh et al reported three fucoidan fractions (SmF1, SmF2, and SmF3) extracted from Sargassum mcclurei where all fractions were found to be less cytotoxic and exhibited inhibition of colony formation in colon cancer DLD-1 cells [ 92 ]. HT-29 cell death is induced by administration of fucoidan, the probable reason for which could be the downregulation of IGF-IR signaling via the IRS-1/PI3K/AKT pathway [ 93 ].…”
Section: Anticancer Potential Of Fucoidan: Insights From Recent Studiesmentioning
confidence: 99%
“…Pathway of IGF signalling regulates the growth in colon cancer cells (HT‐29) by the insulin receptor substrate‐1 (IRS‐1)/PI3K/AKT and Ras/Raf/ERK pathways. Kim and Nam (2018) noticed that fucoidan significantly dampened the IGF‐IR, PI3K and AKT, expression and their phosphorylated forms (p‐IRS‐1, p‐PI3K and p‐AKT). In addition to its effectiveness in inhibition of IGF‐I‐induced phosphorylation of IGF‐IR, PI3K, Shc (IP, IGF‐IR) and phosphorylated IRS‐1 and PI3K (IP, IRS‐1) compared with the control.…”
Section: Biological Activities and Health Benefits Of Fucoidan Polysaccharidementioning
confidence: 99%
“…19 In addition, HT-29 colon cancer cell viability was inhibited by fucoidan, possibly due to the downregulation IGF-IR signaling through the IRS-1/PI3K/AKT pathway. 20 As a significant clinical application, fucoidan has been found to improve the sensitivity of lung and breast cancer to chemotherapeutic drugs, which not only reduced the severity of related side effects, but also reduced the economic burden to patients. 10,11 In addition, many studies have reported that fucoidan also plays an important anti-cancer role in other tumors, including prostate cancer, gastric cancer, liver cancer, and large B cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%